THE EFFECT OF TEAMS GAMES TOURNAMENT MODEL ON STUDENT LEARNING OUTCOMES ON THE HUMAN EXCRETORY SYSTEM MATERIAL IN CLASS XI AT SMA NEGERI 2 PERCUT SEI TUAN - Fadillah, Annisa Dea; Handayani, Dina (Jurnal Pelita Pendidikan, 2025)
This study aims to determine the effect of the teams games tournament model on student learning outcomes on human excretory system material in class XI SMA Negeri 2 Percut Sei Tuan. This research uses quantitative methods with a pseudo-experimental approach. The research design used was non-equivalent control group. The research population includes all students of class XI SMA Negeri 2 Percut Sei Tuan, which consists of 6 classes. The research sample was selected using random sampling technique, class XI 3 SMA as the experimental class and class XI 4 SMA as the control class. The average data of pre-test and post-test of cognitive abilities in the experimental class were 50.44 and 86.44 and in the control class were 52.77 and 79.44. Based on hypothesis testing, for the experimental class and control class obtained tcount = 7.385 and ttable = 2.0017, then tcount > ttable. The results of observations of student activity at meeting one to meeting two have increased, at meeting one by 80% and at meeting two by 87%, it is concluded that there is an effect of the team games tournament model on student learning outcomes on the material of the human excretory system.